Unlocking Land Values to Finance Urban Infrastructure - Peterson, George E. (Washington, DC : World Bank, 2012)
Urban growth throughout the developing world has created a challenge for financing infrastructure. Investment in infrastructure is needed to provide basic services for newly developed parts of urban areas. It is needed to meet the demand for a safer and more reliable water supply, higher standards for the removal and treatment of wastewater and solid waste, and the transportation requirements of a population whose expectations of mobility rise with household incomes. Infrastructure investment also is essential to the economic productivity of cities. This book examines an important additional option for local infrastructure finance: capturing land value gains for public investment. Land values are highly sensitive to infrastructure investment and urban economic growth. Public works projects such as road construction, water supply, and mass transit investment produce benefits that are immediately capitalized into surrounding land values. Many cities in developing countries have underused public lands that would be more valuable if sold and converted into infrastructure assets. Tapping land values was a large part of the investment strategy of Western countries in financing urban infrastructure during the 19th century, when cities were growing most rapidly. As part of the overall financing mix, using land assets for infrastructure finance has several advantages. Most instruments of this type generate revenues upfront, making it easier to finance lumpy investment projects. Mobilizing finance from land transactions also generates price signals that increase the efficiency of urban land markets and help rationalize the urban development pattern.